Development and optimization of danazol co-crystal loaded tablet to treat endometriosis - Patil, Vidya; Jadhav, Shivraj; Mahajan, Sunil (Prospects in Pharmaceutical Sciences, 2025)
Objectives: To develop, optimize, and characterize danazol co-crystal-loaded tablets for enhanced solubility and dissolution in order to improve therapeutic efficacy in endometriosis treatment. Methods: Danazol co-crystals were prepared using various co-formers through a solvent evaporation technique and characterized by FTIR, DSC, and XRD. Co-crystals were formulated into tablets using direct compression and optimized through a 3² factorial design, varying sodium croscarmellose (8—24 mg) and PVP K-30 (4—20 mg) concentrations. Formulations were evaluated for pre-compression properties, physical parameters, disintegration, dissolution, and stability. Results: Danazol-malonic acid co-crystals (1:2 ratio) exhibited the highest solubility enhancement (11.42 ± 0.53 μg/mL, 13.76-fold increase). XRD confirmed the formation of a new crystalline phase with distinct peaks at 19° and 21° 2θ. The quadratic models for both disintegration time (R² = 0.9971) and drug release (R² = 0.9483) demonstrated excellent predictive capability. Formulation VF7 (24 mg sodium croscarmellose, 4 mg PVP K-30) was identified as optimal with rapid disintegration (74.0 ± 3.2 seconds) and superior dissolution (83.6 ± 3.4% at 30 minutes, 95.8 ± 2.0% at 60 minutes) compared to the marketed product (75.2 ± 2.7% at 60 minutes). The optimized formulation maintained stability under accelerated conditions (40°C/75% RH) for three months. Conclusion: The optimized danazol co-crystal tablet formulation successfully overcame the solubility and dissolution limitations of this poorly soluble drug, potentially enhancing bioavailability and therapeutic efficacy while reducing dosing frequency for endometriosis patients. This approach presents a promising platform for improving clinical outcomes and patient compliance in endometriosis management.